X-ray scattering studies of the metastable ferroelectric phase in KDP induced by static electric field - Claudio Marcio Rocha Remédios (Materials Research, 2003)
Potassium dihydrogen phosphate presents a ferroelectric phase below 122 K and a paraelectric phase for T > 122 K. X-ray scattering measurements were performed in order to verify the mechanism of the phase transition from point group C2v19 to C2v¹19 at 119 K induced by DC electric field; in other words, a change of the local site symmetries of the phosphate group occurs from C2 site in the C2v19 point group to Cs in the C2v¹19 point group. This phenomenon was shown by analyzing the behavior of the integrated intensity of the (800), (080), (1600), (0160), (400) and (040) reflections. The curve fitting of these reflections showed the occurrence of a rotation of the phosphate group around the [010] crystallographic direction during the phase transition. This study confirms the observation of this metastable phase obtained by Raman spectroscopy.